A Study of Critical Issues in Education: Evidence Data Analysis in The Context of The Gambia - Abdoulie Jonga; Syahril Syahril; Rifma Rifma (Sustainable Human Capital Development Journal, 2026)
This study investigates critical issues affecting the education sector in The Gambia through evidence-based analysis using both primary and secondary data. The study is situated within the Gambian educational context, where challenges such as inadequate school infrastructure, teacher shortages, unequal access to learning resources, and limited technological integration continue to affect the quality of education, particularly in rural communities. The objective of the study is to identify the major educational challenges influencing student learning outcomes and assess their implications for educational policy and development. A mixed-method research design was employed, combining primary data collected through surveys and interviews with students, teachers, and school administrators, alongside secondary data obtained from government education reports, policy documents, and published academic studies. Quantitative data were analyzed using descriptive and inferential statistical methods, while qualitative responses provided contextual interpretation of the findings. The results indicate that educational inequality remains a major concern in The Gambia. Approximately 68% of respondents identified inadequate teaching and learning materials as a significant barrier to academic performance, while 57% reported that insufficient access to digital technologies negatively affected student learning. Furthermore, schools with lower teacher-student ratios recorded significantly better student performance levels compared to overcrowded schools (p < 0.05). The findings also revealed notable disparities between urban and rural schools in terms of infrastructure, qualified teachers, and access to educational resources. The study concludes that improving educational quality in The Gambia requires increased government investment in school infrastructure, teacher training, digital learning facilities, and equitable resource distribution. The findings provide evidence-based insights for policymakers, educational institutions, and development partners seeking sustainable reforms to strengthen the Gambian education system